“Two Hands Can Save a Life” (International Journal of First Aid Education)
Launching the 2020 World Restart a Heart initiative, the letter notes a global increase in out-of-hospital cardiac rates as a result of the COVID-19-SARS pandemic as well as a worrying decrease in bystander CPR rates and survival rates. For the 60th anniversary of the development of CPR, the letter celebrates the continued importance of CPR (and chest compressions in particular) and the need to train and reassure the public of their ability to save lives with it.